Civil society's quest for democracy in Zimbabwe: origins,barriers and prospects, 1900-2008 - Magure, Booker (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2009)
This thesis is a critical examination of the origins, barriers and prospects for a working class-led civil society as it sought to democratise Zimbabwe's post-colonial state. It is an interdisciplinary but historically informed analysis of how advanced capitalist development promoted the emergence of social movement unionism with a potentiality to advance democracy in Zimbabwe. Despite occurring on a much smaller and thinner scale, the evolution of civil society in colonial Zimbabwe was akin to what happened in 19th century Britain where capitalist expansion presented a foundation for democratisation. However, big underlying barriers exist in Zimbabwe, resulting from various forms of authoritarian structures and forcible mobilisation strategies emanating from colonialism and the protracted war of liberation. ZANU PF's violent reaction to memory contests by non-participants in the war of liberation seeking an alternative political agenda attest to the controversial and polemical nature of struggles over memory and forgetting in contemporary Zimbabwean politics. These structural impediments forestalled the organic growth of civil society in Zimbabwe, thereby explaining its inchoate status and the failure to significantly determine the course of public policy. While recognising the democratic aspirations and capacities of the working class in precipitating political change, this thesis takes into consideration the impact of other factors on state-society relations. These include deepening state barbarism, globalisation, and technological advances in communication, transnational civil society, a dysfunctional economy, migration and remittances. Finally this thesis presents an optimistic scenario about the prospects for civil society and democratisation in Zimbabwe. I argue that the revival of the productive sectors of the economy can possibly strengthen the labour movement and revive its capacities for ushering in a democracy.
Keywords: Civil Society -- Zimbabwe; Zimbabwe -- Politics and government -- 1980; Zimbabwe -- Economic conditions; Zimbabwe -- History